The Cost of Being Perfect: Perfectionism, Impostor Syndrome, and Mental Health in Women vs Men - Nida Din Muhammad; Masooma Rasheed; Saba Shahab Din; Samreen Asghar; Abdul Aziz MS clinical Psychology Scholar, Department of Psychology, The Superior University Lahore., (Dialogue Social Science Review (DSSR), 2025)
The study is focusing on examining how gender as well as perfectionism is predicting the development of impostor syndrome (IS) and the eventual effect it has on mental health outcomes like depression and anxiety. A cross-sectional sampling method was used and 200 working professionals (equalling 100 men and 100 women) in Pakistan took part in the study using validated self-report measures such as Clance Impostor Phenomenon Scale, Frost Multidimensional Perfectionism Scale, and DASS-21. The results were descriptively and inferentially analysed, the research results indicated that perfectionism positively correlates with IS, especially in women, where the results also indicated that a stronger correlation exists with socially prescribed perfectionism. Mediation analysis proved that IS plays an important role in mediating the correlation between perfectionism and the psychological distress. Moreover, female participants had higher IS than their male counterparts, which most probably occurred because women feel more pressure and had to live up to more societal expectations, as well as a certain gender-based role pressure. The results point to IS as a critical psychological issue, which, on the one hand, is determined by personality traits and on the other socio cultural norms. The presented study highlights the necessity of creating gender-tailored interventions to treat perfectionistic thoughts and impostor phenomena with the ultimate goals of enhancing mental health and professional well-being.